BUILDING THE SELF-CONFIDENCE OF SUBANG’S YOUNG GENERATION TO PURSUE FURTHER STUDIES ABROAD: Array - Asep Kurniawan; Mokmin bin Basri (STIESA-PRESS, 2023)
Higher education abroad is one of the key pathways for young people to broaden their horizons, develop their skills, and enhance their career opportunities. However, low levels of self-confidence often become a barrier for the younger generation in taking steps toward seizing this opportunity. In Subang, a regency in West Java, Indonesia, this condition is also prevalent, where young people face challenges in pursuing further studies abroad. In this context, we introduce a community service program aimed at building the self-confidence of Subang’s youth in pursuing higher education abroad. This program involves a series of activities, including workshops, training sessions, mentoring, and outreach events, all designed to provide information, social support, and practical assistance to participants in overcoming the challenges of studying abroad. The implementation method of this program includes collaboration with various stakeholders, such as educational institutions, local government, non-governmental organizations, and local communities. Evaluation of the program's outcomes shows that it has been successful in increasing the self-confidence and readiness of Subang’s youth to continue their studies abroad. Additionally, the program has also improved participants’ awareness and knowledge of the processes involved in studying abroad. Therefore, this community service initiative has had a significant impact on the youth of Subang and has made a positive contribution to regional and national development as a whole.